Oxidação fotoeletroquímica de metanol, etileno glicol e glicerol em CdS, BiVO4 e BiVO4:Zr-Mo:Pt - Oliveira, Cristian Hessel de (2023)
The photoelectrochemical production of hydrogen (H2) from the water splitting reaction in photoelectrochemical cells is a promising alternative for the production of clean and sustainable energy. However, this process still faces some challenges, such as charge carrier recombination, photocorrosion of photoelectrodes, and slow kinetics of the oxidation reaction in the anodic compartment. By using dopants and co-catalysts, charge carrier recombination can be minimized. While the use of sacrificial agents can help to reduce the photocorrosion of the material, as well as increase the activity of the system by replacing the water oxidation reaction. In this work, the study of the oxidation reaction of different biomass-derived alcohols (methanol, ethylene glycol, and glycerol) as substitutes for the water oxidation reaction is performed, where the effect of the increase in the chain length of these alcohols (structure) with respect to the observed activity (reactivity) and inhibition of photocorrosion was investigated. CdS, BiVO4, BiVO4:Zr-Mo, and BiVO4:Zr-Mo:Pt were the photoanodes evaluated. With respect to CdS, the addition of biomass-derived alcohols to the system strongly inhibited the photocorrosion of the material. The use of dopants and co-catalysts in the BiVO4 photoanode increased the activity of the system for photoelectrochemical oxidation, due to the increased light absorption and the decrease in recombination between the charge carriers. And, regardless of the semiconductor, larger photoelectrochemical oxidation currents densities were observed in the presence of biomass-derived alcohols than only in water and, among the alcohols studied, the order of activity was: jMethanol < jEt.Glycol < jGlycerol < jSulfide, indicating that these alcohols act as hole scavengers and the increase in the number of [COH] groups seem to have a positive effect on increasing the activity of the system.